If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ln(5x + -2) = ln(x) Reorder the terms: ln(-2 + 5x) = ln(x) (-2 * ln + 5x * ln) = ln(x) (-2ln + 5lnx) = ln(x) Multiply ln * x -2ln + 5lnx = lnx Solving -2ln + 5lnx = lnx Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '-1lnx' to each side of the equation. -2ln + 5lnx + -1lnx = lnx + -1lnx Combine like terms: 5lnx + -1lnx = 4lnx -2ln + 4lnx = lnx + -1lnx Combine like terms: lnx + -1lnx = 0 -2ln + 4lnx = 0 Factor out the Greatest Common Factor (GCF), '2ln'. 2ln(-1 + 2x) = 0 Ignore the factor 2.Subproblem 1
Set the factor 'ln' equal to zero and attempt to solve: Simplifying ln = 0 Solving ln = 0 Move all terms containing l to the left, all other terms to the right. Simplifying ln = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(-1 + 2x)' equal to zero and attempt to solve: Simplifying -1 + 2x = 0 Solving -1 + 2x = 0 Move all terms containing l to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 2x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + 2x = 0 + 1 2x = 0 + 1 Combine like terms: 0 + 1 = 1 2x = 1 Add '-2x' to each side of the equation. 2x + -2x = 1 + -2x Combine like terms: 2x + -2x = 0 0 = 1 + -2x Simplifying 0 = 1 + -2x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| -15=5(b-3) | | 88=(-5x^2)(x) | | x(x+8)=560 | | 24-3m=12 | | (x^2+14x+85)=0 | | 2.645*2.645+-14x+42=0 | | 480=(x+4)(x) | | y=0.20x+112 | | 45-5c=5 | | x*x-14x+42=0 | | 4p+9p= | | 6x-4y=56 | | 30-6b=6 | | x^2+5x-14=-14 | | 8x+6y=15 | | x^2+15x=160 | | 6/b-5/d | | Y=x^2+14x+49 | | -(4w-v)-(6v-4w)= | | h=-5t(1t)+45 | | y=-x^2+4x+2 | | 4X+17=-43 | | h=-5t(5t)+45 | | y=5x^2+30x+14 | | 3x+3=75 | | 5=-4 | | h=-5t(-5t)+45 | | -5.2*(-0.007)= | | 3y-16=5 | | -5.2*(0.007)= | | -5.2x(0.007)= | | 9y+4=0 |